2016
DOI: 10.2147/amep.s99441
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of interns and residents toward do-not-resuscitate policies in Saudi Arabia

Abstract: ObjectiveDo-not-resuscitate (DNR) orders in Saudi Arabia were first regulated by a fatwa on a national level in 1988, one that excludes the patient and their families from decision making. Although the core of this policy is taken up by all hospitals in Saudi Arabia, there is no homogeneity in implementation. Here, we appraise what interns and residents know of these policies and their attitudes toward DNR.MethodsInterns and residents in four major hospitals in Jeddah, King Abdulaziz University Hospital, Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
55
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 6 publications
9
55
2
Order By: Relevance
“…This is the first descriptive study evaluating the preferences for resuscitation among a sample of Arab (Saudi Arabian) population with a variety of chronic and advanced terminal illnesses. Previous research from Saudi Arabia highlighted the health care provider's views on issues relating to CPR (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first descriptive study evaluating the preferences for resuscitation among a sample of Arab (Saudi Arabian) population with a variety of chronic and advanced terminal illnesses. Previous research from Saudi Arabia highlighted the health care provider's views on issues relating to CPR (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…13 In the studies performed in Islamic countries, it was found that religion affects the decision-making of medical staff about the DNR order which shows the necessity of presence of a single and specific instruction about this order. [14][15][16] The study about Islamic view on the DNR order by Saiyad stated that we should seek treatment in life-threatening conditions and the treatment would become optional when the benefits of therapy are doubted and it is not recommended to continue the treatment if it is futile. On the other hand, Muslim patients have been encouraged to have a testament in order to make decisions regarding the continuation of their treatment process in particular conditions in which they are not able to express their desires.…”
Section: Thismentioning
confidence: 99%
“…The patient’s family or legal guardian needs not be consulted while issuing the order. The same fatwa indicates 6 situations for issuing a DNR order: if the patient arrives dead at the hospital, if the panel of physicians certifies that the illness is untreatable and death is imminent, if the patient is medically unfit for resuscitation, if the patient is suffering from advanced heart or lung disease or repeated cardiac arrest, if the patient is in a vegetative state, and if resuscitation is considered pointless 8. The local guidelines regarding issuing a DNR order entitle a DNR patient to all treatments except for cardiopulmonary resuscitation.…”
mentioning
confidence: 99%
“…The local guidelines regarding issuing a DNR order entitle a DNR patient to all treatments except for cardiopulmonary resuscitation. All interventions that ensure patient’s comfort and dignity will be offered 8. In practice, all hospitals in Saudi Arabia abide by the core of this policy, namely, 3 consultants signing a DNR order.…”
mentioning
confidence: 99%
See 1 more Smart Citation